Association between fasting plasma triglycerides, all-cause and cardiovascular mortality in Czech population. Results from the HAPIEE study - Pikhart, Hynek; Hubáček, Jaroslav; Peasey, A; Kubínová, Růžena; Bobák, Martin (Physiological research, 2015)
Dyslipidemia is the risk factor of cardiovascular disease, but the relationship between the plasma triglyceride (TG) levels and total/cardiovascular mortality has not yet been analyzed in Slavs. The aim of our study was to analyze the association between the fasting TG levels and all-cause/cardiovascular mortality. We have examined 3,143 males and 3,650 females, aged 58.3+/-7.1 years. 729 deaths (274 cardiovascular deaths) have been registered during up to 11.8 years of follow-up. Age-sex adjusted all-cause mortality was higher in individuals with TG values 3.01-4.00 mmol/l (HR 1.37, 95 % CI 1.02-1.83, P=0.035) and over 4.00 mmol/l (HR 1.66, 95 % CI 1.21-2.27, P=0.002) when compared with a reference group (TG 1.41-1.80 mmol/l). Elevated risk remains significant when adjusted for education, marital status and unemployment. When further adjusted for smoking, BMI and dyslipidemia interventions, HR for those in above 4.00 mmol/l group decreased (1.42, P=0.04). The results have been similar when cardiovascular mortality has been examined, however, results reached statistical significance only for the TG over 4.0 mmol/l (P=0.028). Our results confirmed that enhanced plasma levels of plasma triglycerides are dose dependently associated with increased risk of all-cause mortality, however, it seems that individuals with TG values 1.8-3.0 mmol/l are not in higher risk of death.
Keywords: následné studie; Female; kardiovaskulární nemoci; lidé středního věku; Follow-Up Studies; mužské pohlaví; surveillance populace; rizikové faktory; Humans; Triglycerides; Czech Republic; triglyceridy; Cardiovascular Diseases; lidé; Middle Aged; senioři; omezení příjmu potravy; Fasting; ženské pohlaví; Risk Factors; Česká republika; Aged; mortalita; Male; Mortality; Population Surveillance